PENGHARAPAN DI TENGAH PENGHUKUMAN: SEBUAH TEOLOGI KITAB RATAPAN - Samgar Setia Budhi; Farel Yosua Sualang; Triyono Surahmiyoto (Misioner, 2021)
The Book of Lamentations is a book rich in theological reflections on condemnation and hope. The reflection is enriched by the type of literature used, poetry with the lamentation subgenre, and with an acrostic and stratified text structure. The richness and depth of his theological contemplation encourage the research of this book in biblical theology. The purpose of this study is to find biblical theology of punishment and hope according to the Book of Lamentations. The method used in this study is a synthesis method by finding literary forms, book structures, major themes, and developing these themes by investigating the text based on the structure of the book, as well as investigating various supporting literature. Through this research, it was found that the sins of the people can lead to God's judgment and that punishment causes painful suffering. The right response is to recognize sin and repent and hope in God. God's faithful love and mercy are a strong foundation of hope for believers.